2009
DOI: 10.1093/brain/awp111
|View full text |Cite
|
Sign up to set email alerts
|

Causal role of prefrontal cortex in the threshold for access to consciousness

Abstract: What neural mechanisms support our conscious perception of briefly presented stimuli? Some theories of conscious access postulate a key role of top-down amplification loops involving prefrontal cortex (PFC). To test this issue, we measured the visual backward masking threshold in patients with focal prefrontal lesions, using both objective and subjective measures while controlling for putative attention deficits. In all conditions of temporal or spatial attention cueing, the threshold for access to consciousne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
199
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(226 citation statements)
references
References 61 publications
11
199
2
1
Order By: Relevance
“…Indeed, recent investigation showed that the prefrontal cortex (brain area for which pathological gamblers exhibit diminished neural activity during decision-making; Tanabe et al 2007), and especially the dorsolateral part of the prefrontal cortex, play a key role in the development of metacognition. For instance, Del Cul et al (2009) showed that prefrontal lesions could affect subjective reports of visual experience more than visual task performance. Moreover, Slachevsky et al (2001Slachevsky et al ( , 2003 have shown that lesion affecting the prefrontal cortex also affects awareness as well as the monitoring of actions or sensorymotor readjustments.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent investigation showed that the prefrontal cortex (brain area for which pathological gamblers exhibit diminished neural activity during decision-making; Tanabe et al 2007), and especially the dorsolateral part of the prefrontal cortex, play a key role in the development of metacognition. For instance, Del Cul et al (2009) showed that prefrontal lesions could affect subjective reports of visual experience more than visual task performance. Moreover, Slachevsky et al (2001Slachevsky et al ( , 2003 have shown that lesion affecting the prefrontal cortex also affects awareness as well as the monitoring of actions or sensorymotor readjustments.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming a causal role for PFC in subjective report threshold, patients with lesions to rostrolateral prefrontal cortex (rlPFC, BA10) have an increased threshold for producing metacognitive commentaries about a stimulus compared with controls, despite objective performance being matched between groups [19]. The peak correlation between lesion and decrease in subjective report threshold was seen in left BA10 (peak: 232, 54, 26).…”
Section: Neural Basis Of Metacognitive Accuracy (A) Studies Of Metamementioning
confidence: 96%
“…Recent models have been couched in an 'evidence accumulation' framework, in which samples of data are accumulated over time in order to model the temporal evolution of a decision [19,72,73]. Del Cul et al [19] proposed a dual-route evidence accumulation framework in which evidence for behaviour (a forced-choice report of stimulus identity) and evidence for subjective report (visibility) were accumulated separately. The fit of this model could account for the observed decoupling of subjective reports from performance in patients with damage to the PFC (see the study of Maniscalco & Lau [74] for an alternative account).…”
Section: Psychological Determinants Of Metacognitive Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently increasing interest in meta-cognition with developments in its empirical study (Lau, 2008) and quantification (Galvin, Podd, Drga, & Whitmore, 2003). Although, as yet, we know little of relevant neural mechanisms, the prefrontal cortex is strongly implicated (Del Cul, Dehaene, Reyes, Bravo, & Slachevsky, 2009;Fleming, Weil, Nagy, Dolan, & Rees, 2010).…”
Section: Tpj Sts Mpfcmentioning
confidence: 99%